A FAIR BALANCE BETWEEN THE RIGHT TO RELIGIOUS MANIFESTATION AND THE FREEDOM TO CONDUCT A BUSINESS IN THE CASES OF HEADSCARVES BAN IN PRIVATE EMPLOYMENT? - Julija Ilhan; Mustafa T. Karayiğit (Ankara Avrupa Çalışmaları Dergisi)
The contribution questions the preliminary rulings given by the CJEU in Achbita and Wabe and Müller Cases that define the corporate neutrality policies banning wearing of religious clothes in private employment as indirect discrimination. The contribution argues that such corporate neutrality policies, though applied to all employees in the same way, constitute in fact direct discrimination for the devout followers of orthopraxis religions, such as Islam, Judaism and Sikhism, provide preference to employer’s freedom to conduct a business and economic interests over the employee’s right to religious manifestation and social rights, put the right to religious manifestation at the bottom of the hierarchy of grounds of discrimination and cause to economic and social exclusion of such minority employees, notwithstanding the European values.